Citizenship, belonging and attachment in the ‘war on terror’ - Ahmed, Shamila (Critical criminology, 2016)
The ‘war on terror’ has had an enormous impact on citizens’ legal rights and legal status. Using data from interviews with British Pakistani Kashmiri Muslims, this paper explores how the change to citizens’ legal rights and legal status in the ‘war on terror’, the legal dimension of citizenship, has impacted the psychological dimension of citizenship. Through denoting legal rights, equality and status the study revealed the powerful role of the state and the police in shaping citizens’ perceptions of the legal dimension of citizenship. The paper explores how changes to participants’ perceptions of their legal status and legal rights are instrumental in shaping the psychological dimension of citizenship - participants’ sense of loyalty, belonging and attachment to their British identity and their Islamic identity.